Modifikasi Dengan Penambahan Pengumpan Pada Mesin Pencacah Seresah Tebu(Trash Shredder) Dengan Variasi Kecepatan Maju Traktor - Dedy Gusnadi Sianipar (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2020)
PG Pesantren Baru PTPN X is a sugar factory located in East Java and has a large potential for sugar cane litter. Sugar cane litter is a rich in organic material that can be processed into organic fertilizer in the form of compost. This study aims to determine the results of chopping and testing the performance of a modified sugar cane litter chopper machine. The addition of feeders to the implement refers to a sugarcane harvester. The results of this study indicate the category